Dampak Kebijakan Pembatasan Iklan Rokok Terhadap Perilaku Merokok Remaja - R, Ramlah; Usman, Usman; Umar, Fitriani; Nurlinda, Nurlinda; Anggraeny, Rini (FAKULTAS ILMU KESEHATAN UNIVERSITAS MUHAMMADIYAH PAREPARE, 2026)
Adolescent smoking behavior in Pinrang Regency remains high despite government policies restricting cigarette advertising. This study aims to evaluate the effectiveness of these policies on smoking prevalence among adolescents. A descriptive qualitative method was applied with 21 informants, including adolescent smokers, parents, and village staff, through interviews, observation, and documentation. The findings show that the policy has not been fully effective, as adolescents are still exposed to cigarette advertisements via social media and their surroundings. Contributing factors include peer influence, curiosity, lack of parental supervision, and the perception of smoking as a symbol of maturity. Smoking not only causes health problems but also affects social aspects such as academic performance and the risk of dropping out of school. More comprehensive interventions from families, schools, and the government are needed to control adolescent smoking behavior.